The knowledge and attitude of Ghanaian decision-makers and researchers towards health technology assessment. (April 2020) - Addo, Rebecca; Hall, Jane; Haas, Marion; Goodall, Stephen
Abstract: Although health technology assessment (HTA) is intended to provide policymakers with objective information, the likelihood that a health decision-maker (HDM) will use this information is associated with their knowledge, role and perception of the HTA process. In Ghana, policymakers are working towards formalising the use of HTA, but HDM knowledge of and attitude towards HTA are not known. Between March and May 2016, we conducted in-depth interviews and used inductive thematic analysis to explore Ghanaian HDMs (n = 23) and researchers' (n = 4) perceptions of and barriers to HTA and identify ways to promote HTA. We compare our findings with those reported in previous studies conducted in low-and-middle-income countries. Common themes were that resources, political and cultural factors act as barriers to HTA use. Recommendations made in previous studies which were also identified in this study included the need for the development of both human and data capacity, allocating funds to HTA and stakeholder involvement in HTA processes. Specific recommendations made by Ghanaian HDMs and researchers in this study focused on the establishment of an HTA body: its location, the constitution of the appraisal team, the type of evidence to appraise and who makes the final decision. The findings provide important information in the context of current planning to institutionalise HTA in Ghana. Addressing the identified barriers will enable policymakers to maximise the chances of realising the expected benefits of HTA, as participants who are potential producers and end-users are likely to use what they have contributed to. Highlights: As with other LMIC, decision-makers in Ghana have limited knowledge about HTA. The identified barriers to HTA were resources, political and cultural issues. To promote the use of HTA the identified barriers need addressing. Decision-makers were positive about implementing HTA and identified areas of use.